IAPSM’s Position Paper on the Human Papilloma Virus (HPV) Vaccine for Adult Immunization in India - Ranjitha S. Shetty; Anuradha Nadda; Muralidhar Tambe; Abhishek Raut; Kapil Goel; Chythra R. Rao; Aprajita Mehta; Pankaj Bhardwaj; Madhu Gupta; Veena G Kamath (Indian Journal of Community Medicine)
Cervical cancer ranks as the second most common cancer in women in India, primarily caused by persistent infection with the human papillomavirus (HPV). Given its long latent period, secondary prevention through screening and early detection is essential. However, fear and stigma associated with cancers and the costs involved in disease management are the prominent barriers to its uptake. HPV vaccination is one of the vital components of the World Health Organization’s (WHO) Global Strategy to speed up the elimination of cervical cancer as a public health problem. In India, four prophylactic HPV vaccines are currently available. These vaccines are non-infective and highly immunogenic, safe, and effective when administered before HPV exposure. According to WHO recommendations, the primary target group for HPV vaccination consists of girls between the ages of 9 and 14 years. Further, studies have confirmed that both single-dose and two-dose schedules of the HPV vaccine offer comparable efficacy and protection. HPV vaccines are administered intramuscularly in the deltoid region, with 0.5 ml as the standard dose. These vaccines may cause local reactions, as well as mild systemic reactions, such as headache and myalgia, but they are transient. Implementing catch-up vaccination for adolescent girls aged between 9 and 14 years at the time of HPV vaccine introduction would be a cost-effective and sustainable strategy. This would serve as a crucial component of public health efforts to manage HPV infections and eliminate cervical cancer in India.